Assessment of electrochemical compatibility of structural materials of some dental products - Shyogoleva, Mariy; Sevidova, Olena; Vasilchenko, Alexey; Stepanova, Irуna (Trans Tech Publications, 2020)
Orthopedic treatment of tooth anomalies in children and adolescents is provided the long-term use of various metal constructions and devices in the oral cavity – braces, retreaders, locks or rings with struts, wire arches, and so on. They are usually made of corrosion-resistant metals and alloys, most often they are made of stainless chromium-nickel austenitic steels of Х18Н9Т type (import analogue – steel 304), martensitic 08Х17 (import analogue – steel 430), nickel-titanium or nickel-molybdenum alloys. The main disadvantage of all metal products is their manifestation of electrochemical properties and participation in electrochemical processes which can flow into the oral cavity and provoke galvanoses, especially for their joint use. In the "in vitro" conditions, according to a specially developed method, investigations of electrode potentials of directly 4 types of very small (2–3 mm)orthodontic products, in recommended for such products environment were carried out: 3 % solution of sodium chloride (pH=6,8), 2 % solution of citric acid (pH=0.5) and 2 % solution of baking soda (pH=8.65). It is found that the considered elements of orthodynamic systems have similar values of electrode potentials in neutral and weakly-alkaline environments and, accordingly, in the absence of other metal inclusions in the oral cavity, can be used jointly without the risk of galvanosis. The most heterogeneous construction is an individual ring with a strut, in which the difference in the values of the potentials between the individual parts in the acidic medium is more than 120 mV, which is a prerequisite for increasing the likelihood of galvanosis. For simultaneous use of other elements, in particular standard doping brackets, the value of EMF can increase up to 160 mV.
Keywords: electrochemical activity; electrode potentials; galvanosis; metal inclusions